QiShenYiQi Pills, a Compound Chinese Medicine, Prevented Cisplatin Induced Acute Kidney Injury via Regulating Mitochondrial Function - Zhou, Li; Wei, Xiao-Hong; Pan, Chun-Shui; Yan, Li; Gu, You-Yu; Sun, Kai; Liu, Yu-Ying; Wang, Chuan-She; Fan, Jing-Yu; Han, Jing-Yan (Frontiers in Physiology, 2017)
Nephrotoxicity is a serious adverse effect of cisplatin chemotherapy that limits its clinical application, to deal with which no effective management is available so far. The present study was to investigate the potential protective effect of QiShenYiQi Pills (QSYQ), a compound Chinese medicine, against cisplatin induced nephrotoxicity in mice. Pretreatment with QSYQ significantly attenuated the cisplatin induced increase in plasma urea and creatinine, along with the histological damage, such as tubular necrosis, protein cast, and desquamation of epithelial cells, improved the renal microcirculation disturbance as indicated by renal blood flow, microvascular flow velocity and the number of adherent leukocytes. Additionally, QSYQ prevented mitochondrial dysfunction by preventing the cisplatin induced downregulation of mitochondrial complex activity and the expression of NDUFA10, ATP5D and Sirt3. Meanwhile, the cisplatin-increased renal thiobarbituric acid-reactive substances, caspase9, cleaved-caspase9 and cleaved-caspase3 were all diminished by QSYQ pretreatment. In summary, the pretreatment with QSYQ remarkably ameliorated the cisplatin induced nephrotoxicity in mice, possibly via the regulation of mitochondrial function, oxidative stress and apoptosis.